PENGARUH PROPORSI KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL, AUDIT TENURE, REPUTASI KAP, DAN SPESIALISASI AUDITOR TERHADAP KUALITAS AUDIT (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021 – 2024) - Aldryan Rafi Chandra Alim; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of the proportion of independent commissioners, managerial ownership, audit tenure, public accounting firm (KAP) reputation, and auditor specialization on audit quality. The independent variables in this study include the proportion of independent commissioners, managerial ownership, audit tenure, KAP size, and auditor specialization. Meanwhile, the dependent variable in this study is audit quality.The population used in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period, with sampling using a purposive sampling technique. Data analysis in this study was conducted using multiple linear regression analysis with the assistance of IBM SPSS Statistics software version 29.0.The results show that the proportion of independent commissioners and KAP reputation have a significant negative effect on audit quality. Meanwhile, managerial ownership has a significant positive effect on audit quality, and audit tenure and auditor specialization have no significant effect on audit quality.